Minimizing Transfer Time to an ST Segment Elevation Myocardial Infarction Receiving Center: A Modified Delphi Consensus - Mumma, Bryn E. (2014)
Of patients with ST segment elevation myocardial infarction (STEMI), approximately two-thirds present to a hospital not capable of percutaneous coronary intervention. Transfer to a STEMI receiving center delays time to reperfusion in patients with STEMI, but factors that affect this delay have not been well studied. We performed a three-round modified Delphi study to identify system practices that minimize transfer time to a STEMI receiving center. A comprehensive literature review was used to identify candidate system practices. Emergency medical services, emergency medicine, and cardiology experts were invited to participate. Consensus was defined as 80% agreement that a variable was “very important (5)” or “important (4)” with a mean score ≥4.25 or 80% agreement that a variable was “not important (1)” or “somewhat important (2)” with a mean score ≤1.75. In Round 1, participants rated the candidate items and suggested additional items. Individual feedback was provided, and participants discussed items via conference calls before rating them again in Round 2. In Round 3, participants ranked the consensus items from Rounds 1-2 from most to least important, and the mean score for each item was calculated. Of the 98 experts invited, 29 participated in Round 1, 22 in Round 2, and 14 in Round 3. Participants identified 18 system practices that they agree are critical in minimizing transfer time to STEMI receiving centers, with the most important being performance of a prehospital electrocardiogram and having established transfer protocols. These factors should be considered in the development of STEMI systems of care.